Effect of cold plasma and ultrasonic pretreatment on drying characteristics and nutritional quality of vacuum freeze-dried kiwifruit crisps - Danhua Yue; Lin Lin; Rongxing Li; Zhongjun Zhang; Jianfeng Lu; Shaotong Jiang (Ultrasonics Sonochemistry)
The effect of ultrasound and plasma pretreatment on freeze-dried kiwifruit crisps was investigated in this study. Using unpretreated kiwifruit as a control group (CG), the effects of ultrasound (US), plasma-activated water (PAW), ultrasound combined with plasma-activated water (UPAW), plasma-jet (PJ), and ultrasound combined with plasma-jet (UPJ) on the quality of vacuum freeze-dried kiwifruit were investigated. The results showed that all the pretreatments could change the microstructure of the crisps. The microstructure of dried kiwifruit after pretreatment showed more porous structures with different number and size compared to the CG group. The largest pore structure was observed in the UPAW group which had the highest crispness. The activity of water (Aw) of all pretreatment samples was significantly lower than the CG group (P < 0.05). In addition, the UPAW group had the lowest moisture content (4.85 %) and the highest rehydration ratio (288.03 %), indicating the better drying characteristics. Furthermore, the UPAW pretreatment sample showed good appearance with the highest brightness and the lowest color difference (ΔE). The total sugars and total phenolics of the UPAW pretreatment sample were mostly retained, and its flavor was the closest to the CG group. The combination of US and PAW promoted the formation of a larger cavity structure and improved the drying characteristics and physicochemical properties of dried kiwifruit crips. However, all the pretreatments resulted in a decrease in antioxidant capacity, with the least decreasing of the US group and the most decreasing of the UPAW group. Correlation analysis showed that the chlorophyll and vitamin C were the major antioxidants in dried kiwifruit crips. The mechanism of decrease in antioxidant activity of pretreatment, especially UPAW, should be discussed and the effective measure to reduce the change in chlorophyll and vitamin C should be taken in future research.